SNP Markers as a Successful Molecular Tool for Assessing Species Identity and Geographic Origin of Trees in the Economically Important South American Legume Genus Dipteryx. (13th May 2020) - Honorio Coronado, Eurídice N; Blanc-Jolivet, Céline; Mader, Malte; García-Dávila, Carmen R; Aldana Gomero, David; del Castillo Torres, Dennis; Flores Llampazo, Gerardo; Hidalgo Pizango, Gabriel; Sebbenn, Alexandre M; Meyer-Sand, Barbara R V; Paredes-Villanueva, Kathelyn; Tysklind, Niklas; et al.
Abstract: Dipteryx timber has been heavily exploited in South America since 2000s due to the increasing international demand for hardwood. Developing tools for the genetic identification of Dipteryx species and their geographical origin can help to promote legal trading of timber. A collection of 800 individual trees, belonging to 6 different Dipteryx species, was genotyped based on 171 molecular markers. After the exclusion of markers out of Hardy–Weinberg equilibrium or with no polymorphism or low amplification, 83 nuclear, 29 chloroplast, 13 mitochondrial single nucleotide polymorphisms (SNPs), and 2 chloroplast and 5 mitochondrial INDELS remained. Six genetic groups were identified using Bayesian Structure analyses of the nuclear SNPs, which corresponded to the different Dipteryx species collected in the field. Seventeen highly informative markers were identified as suitable for species identification and obtained self-assignment success rates to species level of 78–96%. An additional set of 15 molecular markers was selected to determine the different genetic clusters found in Dipteryx odorata and Dipteryx ferrea, obtaining self-assignment success rates of 91–100%. The success to assign samples to the correct country of origin using all or only the informative markers improved when using the nearest neighbor approach (69–92%) compared to the Bayesian approach (33–80%). While nuclear and chloroplast SNPs were more suitable for differentiating the different Dipteryx species, mitochondrial SNPs were ideal for determining the genetic clusters of D. odorata and D. ferrea . These 32 selected SNPs will be invaluable genetic tools for the accurate identification of species and country of origin of Dipteryx timber.